Karakteristik Antorpometrik dan Biomotor dalam Mengidentifikasi Bibit Atlet Taekwondo: Systematic Review - Septyaning Lusianti; Puspodari1; Muhammad Yanuar Rizky; Wasis Himawanto; M Anis Zawawi (Universitas Negeri Surabaya, 2025)
Background: Talent Identification (TI) is essential to the pursuit of achievement and progress in human development. IT embodies the search and discovery of the most talented individuals who can solve real-world problems. The impact of IT on the advancement of human potential and capital, IT research has implications for individuals and their families, educators and coaches, and stakeholders and policy makers. This systematic review aims to analyze anthropometric factors related to the taekwondo. Methods: The method used is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The database was taken from Pubmed/MEDLINE, Scopus, Web of Science, and Embase. 9 articles were analyzed through objectives, topic suitability, sample size, research protocol, results and discussion. Results: The results of this literature review explain that anthropometric and biomotor factors reveal significant insights and limitations. Anthropometric components are important for taekwondo breeding including various physical measurements that significantly affect performance. The main anthropometric components are weight and height, body mass index, body fat percentage, sitting height and arm reach, endomorphic body type and skeletal muscle mass. Comprehensive biomotor components, including muscle strength, muscle endurance, cardiovascular endurance, speed, acceleration, motor coordination and flexibility. Conclusions: These anthropometric and biomotor components are very important for the success of finding potential taekwondo athletes through a holistic approach to their development.